Fabrication of micro imaging lens - Lin, Weiding. (2009)
Micro-electromechanical systems (MEMS) technology is an enabling tool for fabrication of components, devices and systems in the micro scale. The advancement in MEMS technology has allowed the designation and fabrication of different types of microlenses. In fact, studies on microlenses have been increasing as researchers search and developed various methods and designs to fabricate microlenses for medical purpose etc.